Understanding Microteaching can Change the Attitude towards Teaching - K, Santhoshini; Bhavana, A.R. (International Journal of Psychosocial Rehabilitation, 2020)
Role of a teacher in the present scenario is important as they are the doorway through which children view the society. As a teacher, one must remain positive and stable in mind. This is possible with attitude. Attitude is the prime factor of any individual. For teachers, attitude decides the classroom climate and students behaviour towards them and the society. Attitude is an outcome of present situation comfort zone. To change an attitude of an individual it is necessary to create that comfort zone. Hence an attempt has is been made to check whether strengthening the microteaching skills can uplift the attitude of student teachers. So the investigator has decided to test the pre and post attitude of student teachers of I year B.Ed with treatment which induces the knowledge of teaching via microteaching, its basics, cycle, skills of microteaching and how it has to be used in the classroom. The experimental group was taught the same content with PowerPoint presentation (PPT), video packages which consists of 13 subjects microteaching class sessions with seven basic skills. A live class session with PPT, microteaching session class, group discussion and group practicing were induced for better comprehend of the basics of teaching. Easiness in accessing power point presentation and video package via phones/ tablets and understandability through live classroom sessions, group discussion and practicing theoretical skills one at a time till mastered makes the student teachers more self confident and boldness to face any classroom situation which indirectly changes the attitude towards teaching and subject being taught.